2015
DOI: 10.1093/jee/tov303
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Growth and Survival ofHylurgus ligniperda(Coleoptera: Scolytinae) andArhopalus ferus(Coleoptera: Cerambycidae) Reared on Artificial or Natural Diet at 15 or 25°C

Abstract: Two saproxylic forest insects, Hylurgus ligniperda (F.) (Coleoptera: Scolytinae) and Arhopalus ferus (Mulsant)(Coleoptera: Cerambycidae), were reared on artificial or natural diet at 15 or 25°C to compare larval growth rates and survival. A significant diet by temperature interaction was observed in the growth of H. ligniperda larvae,which developed faster when reared on natural diet at 15°C, but grew faster and pupated significantly earlier when reared on artificial diet at 25°C. However, H. ligniperda surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Once van Haandel et al New Zealand Journal of Forestry Science (2017) 47:18synchronised, batches of stored eggs were incubated at 20 ± 1.5°C. Upon emergence, neonate larvae were transferred in batches of 20 to Petri dishes of artificial diet (a modification of Rogers et al (2002) as described by Romo et al (2015)) and reared at 20 ± 1.5°C until treatment. Pupae were held in Petri dishes of artificial diet at a constant 10 ± 1.5°C until treatment.…”
Section: Collection Of Dose-response Data For Related Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Once van Haandel et al New Zealand Journal of Forestry Science (2017) 47:18synchronised, batches of stored eggs were incubated at 20 ± 1.5°C. Upon emergence, neonate larvae were transferred in batches of 20 to Petri dishes of artificial diet (a modification of Rogers et al (2002) as described by Romo et al (2015)) and reared at 20 ± 1.5°C until treatment. Pupae were held in Petri dishes of artificial diet at a constant 10 ± 1.5°C until treatment.…”
Section: Collection Of Dose-response Data For Related Speciesmentioning
confidence: 99%
“…Arhopalus ferus lay large egg batches; hence, no periods of chilling were required to synchronise the availability of sufficient individuals for rearing. Once hatched, 10 neonate A. ferus larvae were placed in each Petri dish of artificial diet (Romo et al 2015) and reared at 20.0 ± 1.5°C until they were used in tests. Logs are exported from New Zealand within 5 months of harvest, and laboratory studies at a range of temperatures have shown that A. ferus does not pupate in this time (Romo et al unpublished data).…”
Section: A Ferusmentioning
confidence: 99%
“…Previous research on H. ligniperda was oriented towards investigating the compositions and types of associated fungal populations and related bacterial communities, to explore the roles they may play in the invasion process of H. ligniperda [17,18], its life cycle [19,20], and its detection and trapping effectiveness [21]. However, H. ligniperda can damage the host Pinus thunbergii (Parl) alongside other native pests in newly invaded areas.…”
Section: Introductionmentioning
confidence: 99%
“…This can be alleviated by using an artificial diet [ 11 , 12 ]. Scolytine bark beetles have been reared in the laboratory from the egg to the adult stage on natural diets [ 13 , 14 , 15 , 16 , 17 ] and artificial diets [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%